Rescue eaudiobook - Brown, Ryk (Frontiers Saga Part 2: Rogue Castes, 2016)
A leader left behind . . . An Alliance falling apart . . . Friends stranded on an enemy-held world . . . A chance to rediscover long-forgotten truths . . . The new threat will require an immediate response. But first, Jessica and the Ghatazhak must execute a daring rescue in order to secure their future. But to do so, they need the one man they have been trying to protect. The question is . . . Will he agree?